Seeing the human in everyone: Multicultural experiences predict more positive intergroup attitudes and humanitarian helping through identification with all humanity. (November 2020) - Sparkman, David J.; Hamer, Katarzyna
Abstract: Prior research suggests two components of multicultural experiences—contact with cultural members and experiences with cultural elements—predict less prejudice via stronger identification with all humanity (IWAH). However, only one factor of IWAH (bond) was tested, and only United States samples were used. The present research examined both factors of IWAH (bond with, and concern for, all humanity) and used a nationally representative sample from Poland ( N = 974), a more ethnically homogeneous and collectivist culture. We explored the association between multicultural experiences and negative intergroup attitudes (measured via fear of refugees, Islamophobia, and ethnocentrism) and humanitarian helping, and also tested the mediating role of both factors of IWAH on these attitudinal and behavioral outcomes. Results largely replicate and extend prior findings, revealing contact with cultural members directly predicted stronger bond with and concern for all humanity, and less negative intergroup attitudes toward "others" (but not humanitarian helping). In contrast, experiences with cultural elements directly predicted stronger concern for all humanity (but not bond) and greater humanitarian helping (but not intergroup attitudes). Bond with all humanity mediated the association between contact with cultural members and less negative intergroup attitudes, while concern for all humanity mediated the association between both components of multicultural experiences and greater humanitarian helping. Findings support the benefits of multicultural experiences and their association with stronger IWAH and more positive intergroup outcomes beyond the United States, and also indicate unique roles for the IWAH bond and concern factors. Cultural differences, limitations, and future directions are discussed.